Opioid Use in Adults With Low Back or Lower Extremity Pain Who Undergo Spine Surgical Treatment Within 1 Year of Diagnosis. Issue 24 (15th December 2020) - Fatemi, Parastou; Zhang, Yi; Ho, Allen; Lama, Roberto; Jin, Michael; Veeravagu, Anand; Desai, Atman; Ratliff, John K.
Abstract : Study Design: Retrospective longitudinal cohort. Objective: We investigated opioid prescribing patterns amongst adults in the United States diagnosed with low back or lower extremity pain (LBP/LEP) who underwent spine surgery. Summary of Background Data: Opioid-based treatment of LBP/LEP and postsurgical pain has separately been associated with chronic opioid use, but a combined and large-scale cohort study is missing. Methods: This study utilizes commercial inpatient, outpatient, and pharmaceutical insurance claims. Between 2008 and 2015, patients without previous prescription opioids with a new diagnosis of LBP/LEP who underwent surgery within 1 year after diagnosis were enrolled. Opioid prescribing patterns after LBP/LEP diagnosis and after surgery were evaluated. All patients had 1-year postoperative follow-up. Low and high frequency (6 or more refills in 12 months) opioid prescription groups were identified. Results: A total of 25, 506 patients without previous prescription opioids were diagnosed with LBP/LEP and underwent surgery within 1 year of diagnosis. After LBP/LEP diagnosis, 18, 219 (71.4%) were prescribed opioids, whereas 7287 (28.6%) were not. After surgery, 2952 (11.6%) were prescribed opioids with high frequency and 22, 554 (88.4%) with low frequency. Among patients prescribed opioids before surgery, those with high-frequency prescriptions were more likely to continue this pattern postoperatively than those with low frequency prescriptions preoperatively (OR 2.15, 95% CI 1.97–2.34). For those prescribed opioids preoperatively, average daily morphine milligram equivalent (MME) decreased after surgery (by 2.62 in decompression alone cohort and 0.25 in arthrodesis cohort, P < 0.001). Postoperative low-frequency patients were more likely than high-frequency patients to discontinue opioids one-year after surgery (OR 3.78, 95% CI 3.59–3.99). Postoperative high-frequency patients incurred higher cost than low-frequency patients. Postoperative high-frequency prescribing varied widely across states (4.3%–20%). Conclusion: A stepwise association exists between opioid use after LEP or LBP diagnosis and frequency and duration of opioid prescriptions after surgery. Simultaneously, the strength of prescriptions as measured by MME decreased following surgery. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textThis observational study examined opioid prescribing in employed adults without prior prescription opioids who are then diagnosed with low back and lower extremity pain and later undergo spine surgery. More frequent opioid prescribing preoperatively is associated frequent and chronic opioid use after surgery. Additionally, daily opioid dosage decreases following surgery.